A review on the morphology of daimond thin film coating on various types of substrate materials - Hamzah, Esah; Purniawan, Agung; Mohd. Toff, Mohd. Radzi (Faculty of Mechanical Engineering, 2006)
Diamond coatings are employed to yield significant benefits in applications such as for cutting tools, optical lenses, biomedical components, microelectronics, engineering, and thermal management systems. However, several process parameters must be studied to get optimum coating and eliminated disadvantages results. Chemical Vapor Deposition (CVD) technique is commonly used for diamond coating. This paper reports on investigations in the last few years on CVD process and problems associated with it such as gas mixture, substrate materials and coating adhesion. Emphasis is given to achieve process optimization by selection of substrate material and process parameter is controlled to obtain high quality morphology of thin film diamond coating. Some materials are suitable substrate for diamond nucleation and growth. Increase in substrate temperature and %CH4 in H2 in gas mixture can cause an increase in the nucleation and crystal growth rate and grain size, but the diamond quality will be reduced. Whereas increase in reactor pressure will decrease crystal growth but the diamond quality will be improved. Structure and morphology were investigated by Scanning Electron Microscopy (SEM) and diamond thin film quality by Raman Spectra.